2015
DOI: 10.1021/acs.jpcb.5b06458
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of the Two-Liquid Model for Anomalies of Water, HDL–LDL Fluctuations, and Liquid–Liquid Transition

Abstract: After reviewing the protocol-dependent properties of HDA, which thermally anneals to LDA, and the data gap over an unusually large T-range between HDA, LDA, and water, we investigate whether or not, despite HDA's ill-defined state and distinction from a glass, the HDL-LDL fluctuations view of the two-liquid model can explain water's anomalous behavior. An analysis of the density, ρ, compressibility, β, heat capacity, Cp, and thermal conductivity, κ, of water over a monotonic (continuous) path bridging this dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Anomalies are observed in thermodynamic response functions (such as the isobaric heat capacity and the isothermal compressibility) and dynamic properties (such as diffusion, viscosity, and dielectric relaxation) over a wide range of pressures, P, and temperatures, T. These anomalies become more pronounced for supercooled water, and it is generally believed that the unusual properties arise as water adopts a more ice-like structure as the temperature decreases. However, the underlying reasons are fiercely debated (5,11,(14)(15)(16)(17). At ambient pressures, many of the anomalous properties appear to diverge at a temperature, T s , around 228 K leading to the "stability-limit conjecture" in which the liquid becomes unstable below T s (2).…”
mentioning
confidence: 99%
“…Anomalies are observed in thermodynamic response functions (such as the isobaric heat capacity and the isothermal compressibility) and dynamic properties (such as diffusion, viscosity, and dielectric relaxation) over a wide range of pressures, P, and temperatures, T. These anomalies become more pronounced for supercooled water, and it is generally believed that the unusual properties arise as water adopts a more ice-like structure as the temperature decreases. However, the underlying reasons are fiercely debated (5,11,(14)(15)(16)(17). At ambient pressures, many of the anomalous properties appear to diverge at a temperature, T s , around 228 K leading to the "stability-limit conjecture" in which the liquid becomes unstable below T s (2).…”
mentioning
confidence: 99%
“…12,13 On the basis of that sub-T g endotherm, one of us concluded 14 that the corresponding endotherm previously observed on heating annealed high-density solid water had been mistaken as a second T g of water, and that this high-density solid water is an ill-defined state. 20 The intriguing nature of the above-mentioned sub-T g decrease in  made it necessary to study this feature in detail by varying the T and p protocol for glass formation as well as the protocol for studying the glass formed. It also required a corresponding study of C p measured in the same experiment as .…”
mentioning
confidence: 99%
“…However, some studies have shown that the QLL is well developed at the interface of a solid material with ice; therefore, the electrode surface is also likely to be in contact with the FCS. [20] Cyclic voltammograms measured with the Fe(CN) 6 4 À /Fe(CN) 6 3 À reversible redox couple, show a strong dependence on the experimental parameters, including the size of the working electrode, concentration ratio, and the thermal history of the frozen sample. [54a] For concentration ratios higher than 100, voltam- Reproduced with permission from reference [47].…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…At the nanometer range, a liquid phase can remain unfrozen far below its normal freezing point, allowing studies of supercooled liquids. This approach is often used to find the liquid–liquid transition of water in the so‐called “no man's land” ,. Some other properties or phenomena of fundamental interest, e. g., high liquid viscosity, high proton conductance, slip flow at the wall, have also been reported for liquid phases at such small dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation